Evaluation of HBV DNA decay kinetics in patients containing both rtM204V/I mutant and wild‐type HBV subpopulations during tenofovir DF (TDF) monotherapy or combination therapy with emtricitabine (FTC)/TDF. Issue 9 (23rd May 2014) - Liu, Yang; Fung, Scott; Gane, Edward J.; Dinh, Phillip; Flaherty, John F.; Svarovskaia, Evguenia S.; Miller, Michael D.; Kitrinos, Kathryn M.
<x xml:space="preserve">Abstract</x> Tenofovir disoproxil fumarate (TDF) is recommended as treatment for chronic hepatitis B patients harboring lamivudine‐associated resistance mutations (LAM‐R, rtM204V/I ± rtL180M). This study evaluated the clinical response of rtM204V and rtM204I subpopulations to TDF by comparing their early viral load decay kinetics to wild‐type (WT) subpopulations in chronic hepatitis B patients harboring rtM204V/I prior to initiating TDF or emtricitabine (FTC)/TDF therapy. Allele‐specific PCR assays capable of detecting rtM204V or rtM204I subpopulations as low as 0.5% were developed and used to assess patient samples from a Phase 3b study evaluating TDF and FTC/TDF treatment in LAM‐R patients. Baseline samples (n = 280) were quantified for rtM204V/I subpopulations and rtM204V or rtM204I subpopulations were detected in 269/273 (98.5%) baseline samples with a range of 0.7% to >95%. On‐treatment analyses were conducted for seventeen patients (TDF, n = 8; FTC/TDF, n = 9) that harbored baseline WT and either rtM204V or rtM204I (no rtM204V/I mixtures) and HBV DNA ≥1, 000 copies/ml at/after week 4. The median change in HBV DNA through week 12 for WT and rtM204V/I subpopulations was similar, −2.64 and −3.30 log10 copies/ml, respectively, with no significant difference between TDF and FTC/TDF treatment. In conclusion, rtM204V/I subpopulations demonstrate similar early HBV DNA decline kinetics to WT subpopulations during treatment with either TDF or FTC/TDF. These results demonstrate that TDF is similarly active against both WT and rtM204V/I subpopulations in vivo. J. Med. Virol. 86:1473–1481, 2014. © 2014 Wiley Periodicals, Inc.